2014
DOI: 10.1038/ismej.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the microbial metabolism of carbon dioxide and hydrogen in the kangaroo foregut by stable isotope probing

Abstract: Kangaroos ferment forage material in an enlarged forestomach analogous to the rumen, but in contrast to ruminants, they produce little or no methane. The objective of this study was to identify the dominant organisms and pathways involved in hydrogenotrophy in the kangaroo forestomach, with the broader aim of understanding how these processes are able to predominate over methanogenesis. Stable isotope analysis of fermentation end products and RNA stable isotope probing (RNA-SIP) were used to investigate the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 39 publications
0
59
1
1
Order By: Relevance
“…The nevertheless higher-than-expected CH 4 yield in macropods of the present study seemingly contradicts literature findings of extremely low in vivo CH 4 emission (Kempton et al, 1976;Dellow et al, 1988;Madsen and Bertelsen, 2012; also previously contradicted by von Engelhardt et al, 1978), very small populations of foregut Archaea (Evans et al, 2009;Klieve et al, 2012;Ouwerkerk et al, 2009) and the assumed dominance of reductive acetogens as hydrogen sinks in macropods (Godwin et al, 2014). However, as pointed out by Ouwerkerk et al (2005) and Gulino et al (2013), macropods generally seem to harbour rather unique microbe communities with many as yet undescribed species.…”
Section: Effect Of Feeding Regimen and Kangaroo Species On Methane Emcontrasting
confidence: 55%
See 1 more Smart Citation
“…The nevertheless higher-than-expected CH 4 yield in macropods of the present study seemingly contradicts literature findings of extremely low in vivo CH 4 emission (Kempton et al, 1976;Dellow et al, 1988;Madsen and Bertelsen, 2012; also previously contradicted by von Engelhardt et al, 1978), very small populations of foregut Archaea (Evans et al, 2009;Klieve et al, 2012;Ouwerkerk et al, 2009) and the assumed dominance of reductive acetogens as hydrogen sinks in macropods (Godwin et al, 2014). However, as pointed out by Ouwerkerk et al (2005) and Gulino et al (2013), macropods generally seem to harbour rather unique microbe communities with many as yet undescribed species.…”
Section: Effect Of Feeding Regimen and Kangaroo Species On Methane Emcontrasting
confidence: 55%
“…Ciliate protozoa and fungi were also found in similar density levels to those in the rumen (Dellow et al, 1988). Reductive acetogens that reduce hydrogen to acetate were found to be the main hydrogen sink in macropods, supporting the assumed low CH 4 emissions (Gagen et al, 2010;Godwin et al, 2014;Klieve, 2009;Ouwerkerk et al, 2009). Methanogenic archaea were also present, but in much lower density than in the rumen -that is, up to 1000-fold less (Evans et al, 2009;Klieve et al, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…The metab.bookkeep model may be most appropriate to use when the user wants quick computation time or is limited by time series data, the ecosystem has irregular photosynthetic-irradiance relationships, or in nontraditional diel O 2 sampling situations (e.g., Godwin et al 2014). Because metab.bookkeep does not incorporate lightdependent primary production, it would be the model of choice if the user did not have light data.…”
Section: Which Model To Usementioning
confidence: 99%
“…animals are much smaller than found in ruminant livestock, and it has been demonstrated that reductive homoacetogens are effective hydrogen scavengers in the macropodid foregut (Gagen et al, 2010;Godwin et al, 2014), our findings do provide a basis for the persistence of methanogenic archaea in these communities via alcohol-fueled methanogenesis.…”
Section: Discussionmentioning
confidence: 71%